Fecal shedding of equine small strongyle eggs and its practical importance for selective treatment (FAVE Sección Ciencias Veterinarias, 2020)
Small strongyles are the most prevalent and important parasites in grazing horses throughout the world and the widespread development of antihelminthic resistance has prompted in some countries of the northern hemisphere the application of selective treatments (ST) to reduce or delay the development of these phenomena. This strategy is based on determining strongyle fecal egg counts of all herd members and treating only those exceeding a certain threshold or cut off. However, there is an absence of basic information on horses maintained under climatic, grazing or management conditions different from those observed in the northern hemisphere. In this context, the aim of this study was to characterize the elimination of eggs of small strongyles in horses of different ages from 19 farms in the central area of Argentina. Out of a total of 436 horses, 90% showed positive strongyles egg counts and in these animals the count of eggs per gram of feces (epg) was under 200 and over 1,000 in 32% and 22% of the horses respectively. The distribution of strongyle eggs among individuals of all categories was over-dispersed or aggregated with a general epg arithmetic mean of 671.59 ± 789.76 and a value of the inverse aggregation parameter of 0.72 (negative binomial distribution). The age of the animals (foals vs. adults) and the biotypes in the adult category (sports vs. work) influenced the magnitude of the epg values (P
Keywords: horses; small strongyles; Argentina; epg; selective treatment